Effects of age and circadian rhythm on vital parameters and erythrocyte osmotic fragility of donkeys during seasonal changes. - Moses Ayo-Opemipo Olorunfemi; Abdulhakeem Binhambali; Victor Olusegun Sinkalu; Mohammed Babashani; Felix Uchenna Samuel; Joseph Olusegun Ayo (PLoS ONE)
This study investigates the effects of seasonal variations on the erythrocyte osmotic fragility and vital parameters of donkeys Equus africanus asinus at the National Animal Production Research Institute (NAPRI) in Shika, Kaduna State, Nigeria. The research focused on two key periods: the hot-dry season (April) and the rainy season (July). Twelve donkeys were classified into three age groups: young (1-3 years), adult (4-6 years), and old (7-9 years). Blood samples were collected at six-hour intervals over a 24-hour period, while dry-bulb and wet-bulb temperatures were measured to compute the temperature-humidity index (THI). Vital parameters including rectal temperature, respiratory rate, and heart rate were also recorded. Results showed higher dry-bulb temperatures (DBT) during the hot-dry season, with the lowest DBT of 12°C at 00:00 h and the highest of 25.5°C at 18:00 h. Young donkeys exhibited the highest erythrocyte osmotic fragility during the hot-dry season, while old donkeys showed elevated fragility during the rainy season. Results also demonstrated that erythrocyte osmotic fragility varied significantly with age and season, with young donkeys exhibiting the highest fragility during the hot-dry season at a 0.3% NaCl concentration. However, old donkeys showed increased fragility during the rainy season, which shows the influence of both age and environmental conditions on erythrocyte stability. Also, rectal temperatures were higher in young donkeys during the hot-dry season compared to adults, while heart rates showed significant elevation across all age groups during the rainy season. Overall, this study elucidates the physiological adaptations of donkeys to seasonal thermal stress, providing critical insights into their health management and welfare in varying climatic conditions. Understanding these dynamics is essential for optimizing donkey husbandry practices, especially in regions facing climate variability. These findings contribute valuable knowledge to the field of veterinary physiology and highlight the necessity of tailored management strategies to mitigate the impact of seasonal stressors on animal health.